Industrial hygiene, safety still wanting - Abd Razak, Dzulkifli (2004)
While the nation is focused on troubled building projects under the beleaguereh Project Management Consultancy system, equally worrying is a statement on industrial hygiene by the Department of Occupational Safety and Health (DOSH). According to DOSH, of more than 700 premises and another 600odd outlets inspected for industrial hygiene recently, "almost all were given between two weeks and two months to abide by the regulations" (MM, Nov 13). In other words, even if those problems with the flawed buildings were absent, we would still be faced with other problems at the construction sites.